2005
DOI: 10.1002/mrc.1564
|View full text |Cite
|
Sign up to set email alerts
|

Configuration andE/Zinterconversion mechanism ofO(S)-allyl-S(O)-methyl-N-(acridin-9-yl) iminothiocarbonate

Abstract: The configuration and dynamic behavior of O-allyl-S-methyl-N-(acridin-9-yl)iminothiocarbonate (1) and its S-allyl-O-methyl regioisomer (2) were studied using quantum chemical calculations and by applying a novel graphical method to scatter maps obtained from MD simulations for evaluation of an NOE-weighted internuclear distance (r(NOE)). Energy calculations indicated that the Z configuration was predominant for each compound and, further, this was supported both by the calculated chemical shifts and the r(NOE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The two solution-state species were identified as the Z (major) and E (minor) geometric isomers about the N 12 =C 13 double bond based on NOEs for 3a and 3b between H-1 and the protons of the R substituents in the case of the major isomer and between H-1 and the S-methyl protons in the minor isomer. The predominance of the Z isomer is not surprising in the light of previous studies [33].…”
Section: Semicarbazides 2a Esupporting
confidence: 59%
See 1 more Smart Citation
“…The two solution-state species were identified as the Z (major) and E (minor) geometric isomers about the N 12 =C 13 double bond based on NOEs for 3a and 3b between H-1 and the protons of the R substituents in the case of the major isomer and between H-1 and the S-methyl protons in the minor isomer. The predominance of the Z isomer is not surprising in the light of previous studies [33].…”
Section: Semicarbazides 2a Esupporting
confidence: 59%
“…157 ppm and this can only be accounted for by an SH tautomer. This tautomer may exist as either a Z isomer (preferred based on similar work [33]) and/or an E isomer, but the preference nor the existence of an equilibrium was not ascertained. The driving force for favoring such tautomerisation could be attributed to the energy gain arising from the extended conjugated system, based on the strong tendency of an acridine moiety with a C 9 NH R segment to adopt a 9,10-dihydro arrangement.…”
Section: Resultsmentioning
confidence: 99%
“…Determination of the stereochemistry was based on observation of an NOE between H-1Ј and HO-f in 11 after evaluation of the preferred rotamer. Monte Carlo and Molecular Dynamics simulation runs on the geometry-optimized structure in conjunction with direct evaluation of the r NOE (subroutines available in Perch [50] ), an important consideration for the correctness of the structural interpretation based on NOE data, [51] revealed that misinterpretation due to the system dynamics could be safely neglected.…”
Section: Reaction Of Acrolein With 2ј-deoxycytidinementioning
confidence: 99%
“…However, given the nature of the substituents on this double bond−two electron-withdrawing groups at one end and an electron-donating group at the other−rotation about this bond should be facile 21 The pH at which the reaction was conducted (4.6) results in the products being obtained as salts, but since the products appeared to be more stable when protonated, they were preferentially maintained in this state and the NMR data are thus reported for the protonated species. The site of protonation in 6 was evident by the resonance of N-9, which at −277.9 ppm is consistent with it being the site of protonation; 1,3,5,23 upon deprotonation it obligingly resonated at −213.1 ppm.…”
Section: Issn 1424-6376mentioning
confidence: 99%